THE ADDITION EFFECT OF SULPHANILIC ACID TO THE SYNTHESIS OF 3,4-METHYLENEDIOXYBENZALDEHYDE - Feti Fatimah; Sanusi Gugule (Indonesian Journal of Chemistry, 2011)
It was conducted a research about the addition effect of sulphanilic acid to the synthesis 3,4-methylenedioxybenzaldehyde from the isosafrole using reagents of sodium dichromate, sulphuric acid, and sulphanilic acid. The separation and purification of product were performed using the chromatography column. The purity of the result was tested using thin layer chromatography and determination of the melting point. Furthermore, it was identified its structure using infrared spectrophotometer, 1H and 13C nuclear magnetic resonance spectrometry, and mass spectrometry. The experimental result showed that the percentage yield of 3,4-methylenedioxybenzaldehyde with addition sulphanilic acid was 79.54%.